2021
DOI: 10.3389/fimmu.2021.673068
|View full text |Cite
|
Sign up to set email alerts
|

Gender May Influence the Immunosuppressive Actions of Prednisone in Young Patients With Inflammatory Bowel Disease

Abstract: Although the use of glucocorticoids (GC) is well established, the therapeutic response to these agents often shows important interindividual differences, in particular among young patients with inflammatory bowel diseases (IBD). Currently, GC resistance or dependence cannot be predicted by clinical or laboratory findings. The aim of this study was to investigate the association of gender and age with GC efficacy and with the expression of Glucocorticoid-Induced Leucine Zipper (GILZ). One hundred thirty patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…Sex and age differences relating to GR have been implicated in inflammatory bowel disease (IBD) as well [16] which is consistent with our case, where a significant difference in the dysplastic vs. non-dysplastic GRα/GRβ ratio in female patients and in patients > 45 years old was identified. Reports also indicate that female patients with IBD were more likely to develop a dependence on glucocorticoid treatment compared to male patients, who were less likely to relapse after glucocorticoid dose reduction [16]. In general, sex differences have been identified in epilepsy, with FCD being more common in male pediatric epilepsy patients compared to females [17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Sex and age differences relating to GR have been implicated in inflammatory bowel disease (IBD) as well [16] which is consistent with our case, where a significant difference in the dysplastic vs. non-dysplastic GRα/GRβ ratio in female patients and in patients > 45 years old was identified. Reports also indicate that female patients with IBD were more likely to develop a dependence on glucocorticoid treatment compared to male patients, who were less likely to relapse after glucocorticoid dose reduction [16]. In general, sex differences have been identified in epilepsy, with FCD being more common in male pediatric epilepsy patients compared to females [17].…”
Section: Discussionsupporting
confidence: 92%
“…This could be further investigated. Additionally, age played a statistically significant role in glucocorticoid response in these IBD patients, with glucocorticoid-resistant patients being older than responders [16]. GRβ is known to be involved in glucocorticoid resistance in multiple diseases [18,19], so the current findings of GRβ overexpression and a dependency of sex and age in the GRα/GRβ ratio in dysplastic compared to non-dysplastic brain tissue are consistent with findings in other disorders related to inflammatory factors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Men with psoriasis, multiple sclerosis and SLE have a worse prognosis, in contrast to there not being a difference in rheumatoid arthritis ( 79 ). Young women also have a poorer response compared to men to GC therapy for inflammatory bowel disease ( 81 ). Mortality rates generally are higher among women with autoimmune diseases, but this data is difficult to interpret as to whether biological, social, comorbidies, or other factors drive these observations.…”
Section: Steroid-resistance In Myasthenia Gravismentioning
confidence: 99%
“…However, there are some reports of sex differences in the treatment of some of these drugs. For example, in the treatment of inflammatory bowel disease with prednisone, it has been found that women are more dependent on prednisone than men and that the anti‐inflammatory effects of glucocorticoids are reduced in adolescent women because of reduced glucocorticoid receptor activity [69]. In reports on the treatment of RA, methotrexate has been found to be teratogenic in pregnant women and glucocorticoids taken at doses greater than 7.5 mg per day may impair time‐to‐pregnancy (TTP) by direct effects on endometrial and ovarian function and by transient inhibition of the hypothalamic–pituitary‐ovarian axis [70].…”
Section: The Effect Of Sex Differences On the Treatment And Prognosis...mentioning
confidence: 99%